2007
DOI: 10.1097/pep.0b013e318036a25e
|View full text |Cite
|
Sign up to set email alerts
|

Can Exercise Influence Low Bone Mineral Density in Children with Juvenile Rheumatoid Arthritis?

Abstract: Weight-bearing activities should be included in exercise programs for individuals with JIA, although more research is needed to determine the amount, duration, and frequency of weight-bearing activity needed to reduce the risk for low BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…They may need more than this amount of time to show positive effects on health; however, no study has looked at this issue. We may assume that PA could prevent the development of cardiovascular complications especially in obese and T1DM subjects [8,12,28] and may improve bone mineralization in T1DM and JIA children [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…They may need more than this amount of time to show positive effects on health; however, no study has looked at this issue. We may assume that PA could prevent the development of cardiovascular complications especially in obese and T1DM subjects [8,12,28] and may improve bone mineralization in T1DM and JIA children [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13 Jumping has been found to improve hip and lumbar spine bone mass in prepubertal children. [12][13][14][15][16] Lien et al 6 showed that weight-bearing activities for boys are independent predictors of changes in total bone mineral content (BMC). Several recently published studies demonstrate the effect of physical activity, disease activity, corticosteroids, especially before puberty, nutrition, sun exposure, vitamin D, growth, and smoking on the quality of BMD in children with JIA.…”
Section: Introductionmentioning
confidence: 98%
“…Several recently published studies demonstrate the effect of physical activity, disease activity, corticosteroids, especially before puberty, nutrition, sun exposure, vitamin D, growth, and smoking on the quality of BMD in children with JIA. 5,7,10,12,13 Current knowledge on bone health in children with JIA has established that a sedentary lifestyle contributes to secondary impairments in bone health, muscular fitness, and functional limitations, despite advances in pharmacologic treatment of inflammatory diseases. 13 In a review study from 2007, 8 randomized intervention studies showed beneficial effects from weight-bearing exercise for 8 to 16 weeks, 2 and 3 times a week.…”
Section: Introductionmentioning
confidence: 99%
“…In average children, multiple studies show that high-impact exercise can have positive effects on skeletal development [18]. Other studies [19,20] demonstrate that exercise from low magnitude loading to high-impact exercise can be osteogenic in children with chronic disabling conditions. In adults with rheumatoid arthritis (RA), exercise has been proven to increase muscle strength and have positive effects on bone mineral density [21].…”
Section: Potential Secondary Benefits Of Exercisementioning
confidence: 97%